0266 Objective Sleep Duration During the School-Aged Years: Comparisons with Published Guidelines and Normative Values. (27th April 2018) - Gonzalez, R; Bower, J L; Higa-McMillan, C; Beidel, D C; Alfano, C A
Abstract: Introduction: Overall sleep need changes throughout childhood and adolescence. The most widely-cited studies providing normative sleep duration data in children have relied on subjective reports, yet objective sleep measures often produce discordant sleep parameters compared to subjective measures. The current study compared actigraphy-derived sleep duration in a large sample of youth ages 7 to 16 years to published sleep norms (Iglowstein et al., 2003). The percentage of youth at each age meeting the National Sleep Foundation's (NSF) recommended sleep amounts was also examined. Methods: A sample of 250 youth ( M = 11.05, SD = 2.76) recruited from the community in 3 U.S. cities participated. All youth wore actigraphs for one week at home as part of a larger assessment. Results: When examined according to one-year age bands, results showed youth of all ages were sleeping significantly less than previously published on subjective reports ( p's <.05). The largest discrepancies were noted for youth ages 7 to 11 years ( p's < .001). However, more than 90% of youth at each age failed to meet NSF sleep guidelines. As age increased, fewer youth achieved the minimum amount of sleep recommended. This was most apparent among 14 to 16 year olds, a developmental period during which the proportion of youth failing to achieve the minimum amount of sleep recommended increased significantly. Conclusion: Objectively-derived sleep estimates in a large community-based sample suggest that published age-based sleep norms may overestimate total sleep duration in both children and adolescents. Furthermore, an increasing percentage of youth fail to achieve even the minimum amount of sleep recommended by NSF. Clinicians and researchers need to consider the possibility that parent and child reports overestimate actual sleep. Support (If Any): Funded by a Department of Defense, U.S. Army Medical Research and Material grant ( # W81XWH-13–0058) awarded to the last three authors.